Ritos y Mitos de las Mujeres de la Comunidad de Pesillo, parroquia Olmedo, cantón Cayambe, provincia de Pichincha - León Sánchez, Sofía Estefanía (2014)
This paper demonstrates the process of building women's identities through myths and rituals that are performed at different stages of their lives. Myths in the construction of female identities are a tool induction on policy that every woman should be performed in your life to gain recognition in their community and family. Myths inculcate the rules of coexistence and care of your body in relation to its surroundings. The rites instead are awards in the process of change from girl to woman. The allocation of roles through them empowers women in their environment. The rites show the relationship between the energies of nature and ancestral knowledge of women who are women. The theoretical postulates from Rosaldo, Guerrero, Levi-Strauss enhance the epistemic conception of myths and rituals to identify each according to the empirical material obtained in field research.